2010
DOI: 10.1371/journal.pone.0014443
|View full text |Cite
|
Sign up to set email alerts
|

Innate Synchronous Oscillations in Freely-Organized Small Neuronal Circuits

Abstract: BackgroundInformation processing in neuronal networks relies on the network's ability to generate temporal patterns of action potentials. Although the nature of neuronal network activity has been intensively investigated in the past several decades at the individual neuron level, the underlying principles of the collective network activity, such as the synchronization and coordination between neurons, are largely unknown. Here we focus on isolated neuronal clusters in culture and address the following simple, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
71
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 48 publications
12
71
0
Order By: Relevance
“…It was shown that networks ranging from 50 to 10 6 cells can sustain network bursting with statistical features which are almost size independent (Segev et al, 2002). A similar result was reported for isolated clusters in which NB statistics did not dramatically change for networks larger than 100 cells (Shein Idelson et al, 2010; Figures 3A,B). This suggests the existence of regulatory mechanisms that modify the network morphology to sustain specific activity patterns.…”
Section: Network Bursts In Patterned Circuitssupporting
confidence: 88%
“…It was shown that networks ranging from 50 to 10 6 cells can sustain network bursting with statistical features which are almost size independent (Segev et al, 2002). A similar result was reported for isolated clusters in which NB statistics did not dramatically change for networks larger than 100 cells (Shein Idelson et al, 2010; Figures 3A,B). This suggests the existence of regulatory mechanisms that modify the network morphology to sustain specific activity patterns.…”
Section: Network Bursts In Patterned Circuitssupporting
confidence: 88%
“…It has been already observed for isolated clusters (i.e. ‘finite-size’ networks) that the frequency of synchronous network events increased with circuit size [6], [43]. An interesting prosecution of our work would consist of employing a higher number of interacting modules in order to analyze the onset of more complex dynamics, and the emergence of different hierarchical structures.…”
Section: Discussionmentioning
confidence: 95%
“…These modular networks have been useful in experimentally identifying gating mechanisms that control the spread of neural activity among network nodes (Yvon et al, 2005; Feinerman et al, 2008; Levy et al, 2012; Pan et al, 2015), a phenomenon that typically has been studied through computational modeling (Shinozaki et al, 2007; Vogels and Abbott, 2009). In addition, modular networks have been used to study the initiation and maintenance of asymmetries in communication between network nodes, such as master-slave relationships (Baruchi et al, 2008; Shein Idelson et al, 2010; Kanagasabapathi et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have examined the spread of spontaneous network bursts (Baruchi et al, 2008; Shein Idelson et al, 2010; Kanagasabapathi et al, 2011), but there is a relative dearth of data on the transmission of asynchronous firing activity (Reyes, 2003). Here, using multichannel optical stimulation and multisite electrical recordings (Figure 1A), we investigated the representation of stimulation-based inputs in cortical networks, factors modifying these representations during transmission to a downstream node, and the degree to which the downstream node can discriminate among different input patterns.…”
mentioning
confidence: 99%